2012
DOI: 10.1074/jbc.m111.314112
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Lipid Fluxes at Glycerol-3-phosphate Acyltransferase Step in Yeast

Abstract: Background: Excess oleate induces triacylglycerol synthesis and proliferation of lipid particles (LP) in yeast. Results: Oleate-induced LP formation is dependent on the glycerol-3-phosphate acyltransferase (GPAT) isoform Gat1p, which physically interacts with LPs. Conclusion: Formation of oleate-induced LPs depends on active Gat1p (but not Gat2p). Significance: Fatty acid surplus is controlled at the GPAT step with unique contributions from different isoforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Alternatively, Sct1 and Gpt2 may also acylate dihydroxyacetone phosphate to 1-acyl-DHAP, which is subsequently reduced by the Ayr1 reductase to sn1 -acylglycerol-3-phosphate (Athenstaedt and Daum 2000). The acyltransferases and Ayr are predominantly localized to the ER membrane, but, notably, Ayr and Gpt2 also partially localize to the LD (Athenstaedt et al 1999; Athenstaedt and Daum 2000; Marr et al 2012), indicating that at least the first steps in PA synthesis are also LD resident. Gpt2 and Sct1 acyltransferases exhibit different substrate specificities, giving rise to different populations of phospholipids and TAG molecular species (Zaremberg and McMaster 2002; Marr et al 2012).…”
Section: Lipid Dropletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, Sct1 and Gpt2 may also acylate dihydroxyacetone phosphate to 1-acyl-DHAP, which is subsequently reduced by the Ayr1 reductase to sn1 -acylglycerol-3-phosphate (Athenstaedt and Daum 2000). The acyltransferases and Ayr are predominantly localized to the ER membrane, but, notably, Ayr and Gpt2 also partially localize to the LD (Athenstaedt et al 1999; Athenstaedt and Daum 2000; Marr et al 2012), indicating that at least the first steps in PA synthesis are also LD resident. Gpt2 and Sct1 acyltransferases exhibit different substrate specificities, giving rise to different populations of phospholipids and TAG molecular species (Zaremberg and McMaster 2002; Marr et al 2012).…”
Section: Lipid Dropletsmentioning
confidence: 99%
“…In contrast to wild-type cells, mutants defective in Gpt2 acyltransferase are sensitive to oleate supplementation and fail to synthesize TAG and induce LD formation (Marr et al 2012). Oleate may indeed regulate Gpt2 abundance and its activity by phosphorylation; furthermore, Gpt2-containing crescent ER structures that are observed in close vicinity to LDs in the presence of oleate indicate a regulatory crosstalk between LD formation and activity of the initial steps of glycerolipid synthesis (Marr et al 2012). …”
Section: Lipid Dropletsmentioning
confidence: 99%
“…The most prominent of these proteins was Gat1, a glycerol-3-phosphate acyltransferase (GPAT). As the rate-limiting step in the synthesis of triacylglycerol and glycerophospholipids, GPAT catalyzes the esterification of glycerol-3-phosphate with a long-chain acyl-coenzyme A (acetyl-CoA) to initiate the formation of PA ( Cao et al, 2012 ; Marr et al, 2012 ; Wendel et al, 2009 ). We found that mammalian SEIPIN specifically interacted with the corresponding mammalian GPAT orthologs, GPAT3 and GPAT4.…”
Section: Introductionmentioning
confidence: 99%
“…The yeast GPATs share high sequence similarity but differentially contribute to triacylglycerol and phospholipid biosynthetic pathways [21] . In addition Sct1 appears to have a preference for the incorporation of palmitate while Gpt2 is also able to utilize oleate [6] , [22] . Unique expression patterns have been described for each of the animal acyltransferases in adult rodents [10] , [12] and during distinct stages of embryonic development in Xenopus laevis [23] .…”
Section: Introductionmentioning
confidence: 99%
“…The first of these acylation events is specific for the sn-1 position of G3P and is catalyzed by glycerol-3-phosphate acyltransferase (GPAT) ( Figure 1 ) to produce lysophosphatidic acid (LysoPA). The GPAT step is considered the committed and rate-limiting step of the pathway, representing an important control point in the flow of fatty acids and glycolytic metabolites into both functional and structural membrane components, or fat storage in the form of triacylglycerol [4] , [5] , [6] . It is important to highlight that the “acyl-CoA” substrate in the GPAT reaction represents many possible acyl chains varying in length and degree of unsaturation.…”
Section: Introductionmentioning
confidence: 99%